1972
DOI: 10.1007/bf00347433
|View full text |Cite
|
Sign up to set email alerts
|

Heat tolerance, growth and regeneration in three North Sea bryozoans exposed to different constant temperatures

Abstract: Three species of bryozoans --Membranipora membranacea (L.), Electra pilosa (L.) and Conopeum reticulum (L.) --are capable of acclimating to elevated temperatures, above the normal range experienced in nature, when exposed to a gradual increase in ambient temperature. Conspicuous differences in LD 50 values, as a consequence of acclimation, occur between representatives of the same species acclimated and grown at constant temperatures in the laboratory. The tolerance range of these species is influenced by thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 9 publications
4
37
0
Order By: Relevance
“…Morley, personal communication). Additionally, recent work may be revealing that levels of food availability, previously shown by several workers to have little or no effect upon zooid size (Menon 1972;Hunter and Hughes 1994;O'Dea andOkamura 1999, 2000c;O'Dea and Jackson 2002;O'Dea 2003), may be accounting for some of the variation previously observed (Needham et al 2003). Clearly, more investigations are required to further clarify the presence of the temperature size response in bryozoans and also to try and use new techniques to better understand the mechanisms responsible.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Morley, personal communication). Additionally, recent work may be revealing that levels of food availability, previously shown by several workers to have little or no effect upon zooid size (Menon 1972;Hunter and Hughes 1994;O'Dea andOkamura 1999, 2000c;O'Dea and Jackson 2002;O'Dea 2003), may be accounting for some of the variation previously observed (Needham et al 2003). Clearly, more investigations are required to further clarify the presence of the temperature size response in bryozoans and also to try and use new techniques to better understand the mechanisms responsible.…”
Section: Introductionmentioning
confidence: 89%
“…In addition, several studies have shown that the size of zooids in cheilostome bryozoans varies with respect to the ambient temperature in which the zooid developed, both in the wild and under controlled laboratory conditions (Ryland 1963;Menon 1972;Morris 1976;Sile´n and Harmelin 1976;Okamura 1987;Okamura and Bishop 1988;Hunter and Hughes 1994;O'Dea and Okamura 1999, 2000a, 2000b, 2000cO'Dea andJackson 2002, 2003;O'Dea 2003). Results thus far show a clear inverse relationship between temperature and zooid length, zooid width and zooid frontal area.…”
Section: Introductionmentioning
confidence: 96%
“…For colonial animals like bryozoans, the relationship is expressed at the zooid level, and there is a reasonable body of evidence that zooid size is indeed inversely related to temperature. This evidence comes from diverse laboratory-reared material (e.g., Menon 1972, Hunter and Hughes 1994, Atkinson et al 2006, Amui-Vedel et al 2007, O'Dea et al 2007b, diverse field-collected material (e.g., Okamura 1987, O'Dea and Okamura 2000b, 2000c, O'Dea and Jackson 2002, O'Dea 2005, Lombardi et al 2006, and the growth of bryozoans in the field (O'Dea and Okamura 1999; see Okamura et al 2011 for further review) There are other factors that influence the ultimate size of zooids, the most obvious being species-specific colonial growth rules, such as the production of annual growth check lines (O'Dea andOkamura 2000b, O'Dea 2005, Okamura et al unpubl data), substrate irregularities, predation, and competition from other sessile encrusters, the influence of which can be minimized with the judicious rejection of randomly selected zooids as the approach requires (O'Dea andOkamura 2000a, O'Dea 2005). Salinity and food availability (Hageman et al 2009) have also been shown to influence zooid size, yet the effects are minimal in comparison with those of temperature (Okamura 1987, Hunter and Hughes 1994, O'Dea and Okamura 1999, 2000b, O'Dea 2005, O'Dea et al 2007b.…”
Section: Methodsmentioning
confidence: 99%
“…Variation in zooid size in modern day bryozoans is significantly related to the MART in which the colony grew due to the inverse relationship between zooid size and ambient temperature (Menon, 1972; Okamura, 1987; Okamura and Bishop, 1988;Hunter and Hughes, 1994;O'Dea and Okamura, 1999, 2000a, 2000b, 2000cO'Dea, 2005;Lombardi et al, 2006;Amui-Vedel et al, 2007). MART is estimated by measuring the amount of intracolony zooid size variation in fossil bryozoans and applying it to the following linear equation:…”
Section: Approach 1: Zooid-size Approach To Martmentioning
confidence: 99%